Perspectives on Breastfeeding from Mothers with Postpartum Depression Symptoms: A Qualitative Assessment of Antecedents, Barriers, Facilitators, and Intervention Suggestions - Stelson, Elisabeth A; Kulkacek, Laura; Frasso, Rosemary; Hall, Moriah; Guevara, James P (Breastfeeding medicine, 2021)
Postpartum depression (PPD) is one of the most common birthing complications, and studies negatively associate PPD with breastfeeding initiation and continuation. However, little is known about either the breastfeeding experience of mothers with PPD or what resources mothers need for sustained breastfeeding from their perspectives. This study aimed to identify the antecedents, barriers, and facilitators to breastfeeding for mothers with PPD, understand the relationship between self-efficacy and emergent themes, and generate suggestions to inform supportive interventions. Birth mothers who screened positive for PPD and reported breastfeeding were recruited to participate in semistructured interviews. Interviews were transcribed verbatim, and inter-coder discrepancies from double coding were resolved through consensus. Thematic analysis was facilitated using immersion-crystallization methods. Participants identified five antecedent themes that encourage initiation (professional support, infant health, mother's health, cost-effectiveness, and faith), four facilitator themes for sustained breastfeeding (infant connection, decreased stress, personal attributes, and logistical strategies), and seven barrier themes (physical pain, infant nutrition, negative feelings, latching difficulties, medical conditions, public breastfeeding, and sleep). Participants' suggestions fell into three primary themes: supportive services, managing expectations, and respecting self-determination. Antecedent and facilitator themes did not overlap, indicating that factors encouraging breastfeeding initiation differ from sustaining factors. Participant suggestions, barriers, and facilitators did not largely differ from mothers PPD in other qualitative studies. Therefore, interventions should tailor support to specific breastfeeding phase and may not need to be markedly different for mothers with PPD, in addition to depression management.